2021
DOI: 10.3389/fpsyg.2020.608522
|View full text |Cite
|
Sign up to set email alerts
|

The Late Positive Potential as a Reliable Neural Marker of Cognitive Reappraisal in Children and Youth: A Brief Review of the Research Literature

Abstract: The mental health of young people is a growing public health concern. With socio-emotional difficulties in youth often resulting in psychiatric disorders later in life and most with mental health conditions rather stabilizing in time, it is essential to support healthy socio-emotional development. With a comprehensive definition of mental health, since emotion regulation (ER) plays a critical role in prevention, it becomes imperative to better understand how children effectively manage their emotions from an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…We used self‐reported emotional feeling and the late positive potential (LPP) as subjective and objective measurements of emotion to provide cross‐modal evidence. The LPP is a sensitive electrophysiological indicator of emotional reactivity (Y. Liu, Huang, McGinnis‐Deweese, Keil, & Ding, 2012), and a large amount of evidence has revealed reliable associations between LPP amplitude and emotion regulation effect of reappraisal (Kennedy & Montreuil, 2021). Specifically, downregulating negative emotion via reappraisal is associated with decreased LPP amplitudes (Hajcak & Nieuwenhuis, 2006; He, Zhao, et al, 2020; Zhao et al, 2021), whereas upregulating positive or neutral emotion (i.e., increasing positive attitude) via reappraisal is associated with enhanced LPP amplitudes (Langeslag & van Strien, 2013; W. Liu, Liu, Chen, Jiang, & Shang, 2019; Y. Wang, Liao, Shangguan, Shang, & Zhang, 2020; Wilson & MacNamara, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used self‐reported emotional feeling and the late positive potential (LPP) as subjective and objective measurements of emotion to provide cross‐modal evidence. The LPP is a sensitive electrophysiological indicator of emotional reactivity (Y. Liu, Huang, McGinnis‐Deweese, Keil, & Ding, 2012), and a large amount of evidence has revealed reliable associations between LPP amplitude and emotion regulation effect of reappraisal (Kennedy & Montreuil, 2021). Specifically, downregulating negative emotion via reappraisal is associated with decreased LPP amplitudes (Hajcak & Nieuwenhuis, 2006; He, Zhao, et al, 2020; Zhao et al, 2021), whereas upregulating positive or neutral emotion (i.e., increasing positive attitude) via reappraisal is associated with enhanced LPP amplitudes (Langeslag & van Strien, 2013; W. Liu, Liu, Chen, Jiang, & Shang, 2019; Y. Wang, Liao, Shangguan, Shang, & Zhang, 2020; Wilson & MacNamara, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The LPP is a sensitive electrophysiological indicator of emotional reactivity (Y. Liu, Huang, McGinnis-Deweese, Keil, & Ding, 2012), and a large amount of evidence has revealed reliable associations between LPP amplitude and emotion regulation effect of reappraisal (Kennedy & Montreuil, 2021). Specifically, downregulating negative emotion via reappraisal is associated with decreased LPP amplitudes (Hajcak & Nieuwenhuis, 2006;Zhao et al, 2021), whereas upregulating positive or neutral emotion (i.e., increasing positive attitude) via reappraisal is associated with enhanced LPP amplitudes (Langeslag & van Strien, 2013;W.…”
mentioning
confidence: 99%
“…Preliminary evidence suggested that late positive potential (LPP) may serve as an indicator of a sustained increase in neural activity following the presence of emotional stimuli. Most tests of emotion regulation of LPP are based on the magnitude of LPP amplitude, which reflects the ability to use emotion regulation for cognitive reappraisal (Kennedy and Montreuil, 2020). Some studies have found a significant increase in LPP amplitudes in depressed individuals for negative stimuli (Dainer-Best et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, our results of enhanced LPP amplitude in postassessment differed from other studies, which rather showed an attenuation in LPP amplitude after emotion regulation intervention. 12 This difference could be due to the complex implicit task used in those studies, where unpleasant picture stimuli were simultaneously presented with reappraisal instructions. 13 Our study sheds light on the process of letting go grudges through forgiveness in patients who had undergone interpersonal hurt, after exposing them to FT. To the best of our knowledge, there is a paucity of studies that delineate the process backed by ERP-based evidence.…”
Section: Letting Go Of Grudges: An Intervention-based Erp Study Among...mentioning
confidence: 96%
“…However, our results of enhanced LPP amplitude in post- assessment differed from other studies, which rather showed an attenuation in LPP amplitude after emotion regulation intervention. 12 This difference could be due to the complex implicit task used in those studies, where unpleasant picture stimuli were simultaneously presented with reappraisal instructions. 13 …”
mentioning
confidence: 96%